Topografias discursivas e ethos em canções praieiras de Dorival Caymmi - Lima, Germana Moreira (2022)
The so called canções praieiras are the work of singer songwriter Dorival Caymmi, becoming one of his most recognized musical aspects in the Brazilian music scene, mainly for portraying the sea and its relationship with the culture, customs and beliefs of those who live on the coast of Bahia. From this point of view, the present research intends to analyze the construction of discursive topographies and ethos in the lyrics of canções praieiras. For this purpose, we took as theoretical support the French Discourse Analysis from the perspective of Maingueneau (1996a/b, 1997, 2000, 2001, 2004, 2005, 2006a, 2006b, 2008, 2010a/b). In addition to the topography, we present the scenography and all the components linked to it as the main concepts of this research enunciator, co enunciator, chronography and ethos. In the analysis of the corpus, we explain how the scenography contributes to the construction of the topography i n the beach songs by Dorival Caymmi; we investigated how these topographies in the scenographic investment also build the ethos of the subjects in the lyrics of these songs. According to the results obtained, we can consider that, in relation to the topogr aphies, they are eminently coastal, in view of the predominance of the figure of the sea, which, in our view, acts both in a geographical and a metaphysical dimension; as well as topographies related to places around the sea are presented, such as the stre et where religious festivals take place, the surroundings of earthly sanctuaries such as the churches of Nossa Senhora da Conceição da Praia, Igreja da Boa Viagem, in addition to other spaces. as the pier in the port of Salvador. We can also verify that th ese dimensions collaborate for the constitution of the ethé of the enunciators, prevailing a devout ethos, which is characterized by the mixture of beliefs of African, European and indigenous roots. Thus, such practices also evoke the festive spirit of the se subjects. The ethé represented by the female figure (woman, bride, mother) are also evident, who are divided between suffering and conformism, such as the orixá Iemanjá, referred to in various ways as the mermaid of the sea, lady of the waters, etc., an d the ethos of the fisherman who is marked by the heroic, hardworking figure, attached to the sea, and the Iemanjá to whom he is devoted and to whom he is attracted